Implementation on the Pedagogic Competence on Learners Characteristics Aspect of History Teacher Class XI MAN 1 Probolinggo - Dwi Sulistiyoningsih; Bambang Soepeno; Sumarno Sumarno (JURNAL HISTORICA, 2018)
Learners have different characteristics, teachers required teachers are required to understand the characteristics of learners. Understanding teacher against the characteristics of learners assist teachers in providing educational services for learners in accordance with its characteristics. The problems in this research is how understanding history teacher against the competency of pedagogic on the characteristics of learners class XI IIS MAN 1 Probolinggo. This research aims to describe against the competency of pedagogic on the characteristics of learners class XI IIS MAN 1 Probolinggo. The approach in this research is approach qualitative. The subject of the research is history teacher class XI IIS MAN 1 Probolinggo. Engineering data collection with the method obsevasi, interviews and documentation. Validity of the test with the test triangulansi. The results of this research about some things, first understand history teacher on the differences of physical development of the learner, second understand history teacher on the differences of intellectual development of the learner, third understand history teacher on the differences of emotions development of the learner, fourth understand history teacher on the differences of social and moral development of the learner. Keywords : Pedagogic Competence, Understanding, Characteristic of Learners.